Efficacy and Mechanism of Panax Ginseng in Experimental Stroke - Liu, Lei; Anderson, Gigi A.; Fernandez, Tyler G.; Doré, Sylvain (Frontiers in Neuroscience, 2019)
Stroke is one of the leading causes of death and long-term disability worldwide. However, effective therapeutic approaches are still limited. The disruption of blood supply triggers complicated temporal and spatial events involving hemodynamic, biochemical, and neurophysiologic changes, eventually leading to pathological disturbance and diverse clinical symptoms. Ginseng (Panax ginseng), a popular herb distributed in East Asia, has been extensively used as medicinal and nutritional supplements for a variety of disorders worldwide. In recent years, ginseng has displayed attractive beneficial effects in distinct neurological disorders including stroke, involving multiple protective mechanisms. In this article, we thoroughly reviewed the literature on ginseng studies in experimental stroke published before June 30, 2018, particularly focusing on the in vivo evidence on the preventive or therapeutic efficacy and mechanisms of ginseng in various stroke models of mice and rats. We summarized the efficacy of ginseng and ginsenosides on short- and long-term stroke outcomes, as well as the underlying mechanisms. This review provides new insights into the comprehensive understanding of the pharmacological activities of ginseng that benefit stroke prevention and recovery.